"Una Vida Toda de Fantasías”: The Fantastic in the Theatre of Alejandro Casona - Álvarez Álvarez, María (Tropelías: Review of Literary Theory and Comparative Literature, 2019)
The present paper aims to study the presence of the fantastic in the theatre of Alejandro Casona, one of the fundamental traits that critics have pointed out in his work. In his plays, the fantastic acquires vital importance for the development of the action, and the real and unreal levels melt and nourish each other, without one can fully exist without the other. Therefore, we will also study the procedures used by the author to configure the fantastic in his works, focusing on a selection of titles: Otra vez el Diablo, La sirena varada, La dama del alba, La barca sin pescador, La casa de los siete balcones, Prohibido suicidarse en primavera and Los árboles mueren de pie.
Keywords: 20th Century Theatre; Alejandro Casona; Contemporary Theatre; Generación del 27